4(2x-1)-(-3x-5)=-179

Simple and best practice solution for 4(2x-1)-(-3x-5)=-179 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-1)-(-3x-5)=-179 equation:


Simplifying
4(2x + -1) + -1(-3x + -5) = -179

Reorder the terms:
4(-1 + 2x) + -1(-3x + -5) = -179
(-1 * 4 + 2x * 4) + -1(-3x + -5) = -179
(-4 + 8x) + -1(-3x + -5) = -179

Reorder the terms:
-4 + 8x + -1(-5 + -3x) = -179
-4 + 8x + (-5 * -1 + -3x * -1) = -179
-4 + 8x + (5 + 3x) = -179

Reorder the terms:
-4 + 5 + 8x + 3x = -179

Combine like terms: -4 + 5 = 1
1 + 8x + 3x = -179

Combine like terms: 8x + 3x = 11x
1 + 11x = -179

Solving
1 + 11x = -179

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 11x = -179 + -1

Combine like terms: 1 + -1 = 0
0 + 11x = -179 + -1
11x = -179 + -1

Combine like terms: -179 + -1 = -180
11x = -180

Divide each side by '11'.
x = -16.36363636

Simplifying
x = -16.36363636

See similar equations:

| 10b+5=76+5 | | 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 | | 5(x+8)-2x=60 | | 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 | | 48x+6=246 | | y=x^2+12+35 | | 5-3x=4x+12 | | 6-3A+5B=0 | | (-9x+11)8= | | 3z^3+6z^2=72z | | 1/3X-1-1/4X+2=3 | | 23=11x+1 | | 9=-2x+4 | | 7(p+1)=p-9 | | C=3.14(5) |

Equations solver categories